Magnetic carbon composites with a hierarchical structure for adsorption of tetracycline, prepared from sugarcane bagasse via hydrothermal carbonization coupled with simple heat treatment process - Natthanan Rattanachueskul (2018)
© 2016 Elsevier Ltd Sugarcane bagasse, an agricultural waste, was successfully converted into novel magnetic carbon composites by low temperature hydrothermal carbonization at 230 °C for 24 h, followed by heat treatment at 400 °C for only 1 h in air. Effects of NaOH and iron loading on the chemical properties of the composites were studied. In addition, various techniques were employed to investigate the physicochemical properties of the composites. Adsorption kinetics and isotherms were investigated with tetracycline (TC) for the magnetic composites. The magnetic carbon composite exhibited 48.35 mg/g maximum adsorption capacity and was highly stable chemically and mechanically, with also good magnetic properties. The adsorption of TC by the magnetic adsorbent was mainly attributed to H-bonds and π-π interactions. The results indicate that waste sugarcane bagasse from the sugar industries can be efficiently transformed to a magnetic adsorbent for TC removal via a facile environmentally friendly method.